The song remains the same. - Macpherson, Alex (New Humanist)
The article offers information on the uses of music software Spotify for those who love listening to music focusing on the culture of music. It mentions that the technology used by Spotify can help users create music libraries and also curate them. Topics discussed include the algorithms used in the software, playing of songs according to moods and the music streaming feature of the software.